Identification and evaluation of potential microRNA markers for diagnostics in neurodegenerative diseases and correlation with other biochemical markers - Richard Novobilský; Pavlína Kušnierová; Dominik Štěpán; Petra Bártová; David Stejskal; Michal Bar (PLoS ONE, 2025)
Objectives MicroRNAs (miRNA) are short, non-coding RNA molecules that play a crucial role in the development of organisms and are involved in various biological processes. They are considered potential biomarkers for many diseases, including neurodegenerative diseases. This study aimed to identify a set of microRNA targets that exhibited the greatest potential in successfully distinguishing and differentiating neurodegenerative diseases and to establish a correlation between selected miRNAs across different diagnostic groups. Methods The study included the analysis of 126 patients. The patients were divided into five diagnostic groups – Alzheimer’s disease, non-Alzheimer’s dementia, Movement disorder, Dementia and movement disorder, and Healthy controls. The circulating RNA was isolated using the iCatcher Circulating cfRNA 1000 Kit with the iCatcher 12 automated isolator. The determination of microRNA was performed by TT-qPCR in the CFX96™ Real-Time Detection System. The concentrations of the remaining biomarkers were determined by ELISA. The statistical data were processed using MS Excel and MedCalc® software. Results The following miRNAs were studied based on the primary screen for identification of potential microRNA targets and published literature data:hsa-miR-23a-3p, hsa-miR-29c-3p, hsa-miR-30b-5p, hsa-miR-142a-5p, hsa-miR-146a-5p, hsa-miR-151a-3p.A statistically significant correlation was identified between hsa-miR-29c-3p and hsa-miR-30b-5p, hsa-miR-30b-5p and hsa-miR-151a-3p, hsa-miR-23a-3p and hsa-miR-29c-3p, hsa-miR-23a-3p and hsa-miR-151a-3p, between hsa-miR23a-3p and hsa-miR-30b-5p, between hsa-miR-142a-5p and hsa-miR-146a-5p, hsa-miR-142a-5p and hsa-miR-151a-3p as well as between hsa-miR-146a-5p and hsa-miR-151a-3p.Significant differences were observed in hsa-miR-23a-3p and hsa-miR-29c-3p among different diagnostic groups. Compared to classical biomarkers of dementia, significant correlations were observed between plasmatic amyloid-β peptide 42 and hsa-miR-29c-3p, hsa-miR-142a-5p, hsa-miR-146a-5p, hsa-miR-151a-3p. Similar correlations were also found with the plasmatic amyloid-β peptide ratio of 42/40. Conclusions The most promising microRNAs for differentiating among neurodegenerative diseases are hsa-miR-23a-3p and hsa-miR-29c-3p. Additionally, there is a correlation between hsa-miR-29c-3p and amyloid-β peptide and the ratio of amyloid-β peptide 42/40.While more robust studies are necessary, there could be a potential for utilizing this miRNA as a therapeutic agent in the future.